Ametoctradin + dimethomorph spray frequency affects late blight disease and yield in potato genotypes - Anoumaa, M.; Suh, C.; Kouam, E.B.; Kanmegne, G.; Djomo, S.H.; Temfack, D.C.D.; Fonkou, T. (2025)
Potato (Solanum tuberosum L.) production is hindered by several diseases, the worst being the late blight disease caused by Phytophthora infestans (Mont) de Bary. This study aimed at determining an appropriate frequency of ametoctradin + dimethomorph ([26.9 + 20.2]%) spray for late blight disease management in potato genotypes. Field experiments were conducted in Bansoa, Cameroon, from August to October in 2019 and 2020 growing seasons The experimental design was a split‐plot design with three replications. Three ametoctradin + dimethomorph spray frequencies (4‐, 7‐, and 10‐day intervals) were tested at the plot level, whereas seven genotypes including Banso, CIPIRA, Desiree, Dosa, Jacob2005, Manate, and Tezelfo were tested at the subplot level. The commonly used fungicide combination, which includes Mancozeb 80% wettable powder supplemented with cymoxanil + chlorotalomil [(30 + 6)%] wettable powder, was sprayed at 3‐day intervals (a total of 18 sprays) and was used as a positive control. Negative control plots were not sprayed. Data were collected on late blight rAUDPC (relative area under the disease progress curve) and yield components. Results showed all fungicide spray frequencies reduced rAUDPC and consequently increased potato yield. The most economically efficient spray frequency was the 7‐day interval with a total of nine sprays, which resulted in an increased net return of $9738 ha−1 with 9.6% profitability against the commonly used fungicide mix. The total number of fungicide sprays could be reduced to six for genotypes Banso and CIPIRA, which showed lower rAUDPC. The mean yield loss associated with unsprayed plots was 93.2%.